Politeness Strategies and Diplomatic Identity: A Pragmatic Analysis of Prabowo Subianto’s UN General Assembly Speech - Ratnawati, Ratnawati; Sulastri, Sulastri; Idrus, Nur Abidah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
In political communication, language serves not only as a medium of communication but also as a strategic tool for diplomacy and image building. This study investigates the pragmatic politeness strategies employed by Prabowo Subianto in his United Nations General Assembly speech. This research aims to identify the types of pragmatic politeness strategies employed in his speech, uncover how these strategies reflect intercultural awareness and diplomatic intent. Guided by Searle’s (1979) speech act theory and Brown and Levinson’s (1987) politeness theory, this qualitative descriptive research analyzes the speech transcript through pragmatic analysis. The findings reveal that Prabowo utilizes four speech acts (assertive, directive, commissive, and expressive) and all politeness strategies (positive politeness, negative politeness, bald on record, and off record), such as solidarity, mitigating face threats in his speech to express solidarity, respect, and inclusivity toward a diverse global audience. These strategies reflect intercultural sensitivity by emphasizing respect, inclusivity, cooperation, aligning with the conventions of global political discourse, and achieving persuasive and diplomatic effects. Furthermore, the pragmatic functions of these strategies contribute to projecting Indonesia as a peace-oriented, collaborative, and globally responsible nation. The study highlights how pragmatic politeness in political communication serves diplomatic purposes, reinforces the role of language as a bridge in international relations. The study concludes that Prabowo’s strategic use of politeness is central to constructing Indonesia’s diplomatic identity as a collaborative and responsible global actor.